2019
DOI: 10.1001/jamapsychiatry.2018.3658
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Comorbidity Within Mental Disorders Among a Danish National Population

Abstract: IMPORTANCE Individuals with mental disorders often develop comorbidity over time. Past studies of comorbidity have often restricted analyses to a subset of disorders and few studies have provided absolute risks of later comorbidity. OBJECTIVES To undertake a comprehensive study of comorbidity within mental disorders, by providing temporally ordered age-and sex-specific pairwise estimates between the major groups of mental disorders, and to develop an interactive website to visualize all results and guide futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
351
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 446 publications
(395 citation statements)
references
References 28 publications
39
351
1
4
Order By: Relevance
“…There is very high comorbidity among the psychiatric cases in the iPSYCH cohort (Schork et al 2019b), and, for gastrointestinal infections, around 93% of the people who had gastrointestinal infections were also diagnosed with at least one other infection category from the previous section. It has been shown that individuals with one psychiatric diagnosis are more prone to getting another one, and this higher "comorbidity risk" can persist over time, as reported for a much larger Danish dataset (Plana-Ripoll et al 2019). We, therefore, adopted two approaches: in one approach, controls cannot have any psychiatric diagnosis or any infection category for their respective phenotype (super controls); for example, in the genome-wide association study (GWAS) for gastrointestinal infections, we excluded individuals who had other infection categories from being controls.…”
Section: Defining Cases and Controlsmentioning
confidence: 67%
“…There is very high comorbidity among the psychiatric cases in the iPSYCH cohort (Schork et al 2019b), and, for gastrointestinal infections, around 93% of the people who had gastrointestinal infections were also diagnosed with at least one other infection category from the previous section. It has been shown that individuals with one psychiatric diagnosis are more prone to getting another one, and this higher "comorbidity risk" can persist over time, as reported for a much larger Danish dataset (Plana-Ripoll et al 2019). We, therefore, adopted two approaches: in one approach, controls cannot have any psychiatric diagnosis or any infection category for their respective phenotype (super controls); for example, in the genome-wide association study (GWAS) for gastrointestinal infections, we excluded individuals who had other infection categories from being controls.…”
Section: Defining Cases and Controlsmentioning
confidence: 67%
“…This literature has demonstrated a high degree of co‐occurrence between AUD and other mental disorders, with a particularly strong association between AUD/substance use disorders (SUDs) and other externalizing disorders (e.g., antisocial personality; see Kessler, for a review). From a clinical and public health perspective, the impact of comorbid conditions on individual outcomes is substantial (e.g., Cohen et al, ; Grant et al, ; Plana‐Ripoll et al, ), yet relatively little research has examined the severity of comorbid psychiatric disorders across psychopathology domains (e.g., externalizing, internalizing) with AUD. The ability to assess the extent to which the comorbid disorders (e.g., symptom count, severity) covary with AUD is limited given that most studies examining comorbidity rely on categorical representations of the disorders, consistent with the diagnostic systems that were in place at the time of the research (e.g., previous versions of the DSM).…”
Section: Comorbidity Of Aud With Psychiatric Disordersmentioning
confidence: 99%
“…Understanding the biological basis of sex differences in human disease, including neuropsychiatric disorders and traits, is critical for developing sex-informed diagnostics and therapeutics and realizing the promise of precision medicine [4]. Moreover, genetic variants with sex-differentiated effects across multiple traits may influence patterns of comorbidity for neuropsychiatric disorders and related behavioral traits, suggesting the need for cross-disorder genetic analyses to be evaluated in the context of sex-specific effects [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%